2021
DOI: 10.3892/mmr.2021.12250
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated inflammation may predispose patients with serious mental illnesses to severe COVID‑19 (Review)

Abstract: Genetic and nongenetic factors associated with an increased inflammatory response may mediate a link between severe coronavirus disease 2019 (coVid-19) and serious mental illness (SMi). However, systematic assessment of inflammatory response-related factors associated with SMI that could influence COVID-19 outcomes is lacking. In the present review, dietary patterns, smoking and the use of psychotropic medications are discussed as potential extrinsic risk factors and angiotensin-converting enzyme (ace) inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 142 publications
(183 reference statements)
0
7
0
Order By: Relevance
“…Dietary methyl-donors taking part in one-carbon metabolism affect several metabolic processes as well as age and metabolic state-specific DNA methylation, which is necessary for the healthy regulation of gene transcription and thus healthy metabolic regulation [ 1 , 3 , 22 , 32 , 33 , 34 ]. Reports and studies during on COVID-19 showed that both the very low and too high concentration of vitamins B and D, micronutrients and minerals make the human body vulnerable to chronic diseases or infections [ 35 , 36 , 37 , 38 ]. Indeed, we also found that the dietary intake of methyl-donors such as methionine, B6, B9 and the summative amounts of methyl-donor intakes (SUM MD) in terms of RDA levels significantly increased the overall survival of breast and colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary methyl-donors taking part in one-carbon metabolism affect several metabolic processes as well as age and metabolic state-specific DNA methylation, which is necessary for the healthy regulation of gene transcription and thus healthy metabolic regulation [ 1 , 3 , 22 , 32 , 33 , 34 ]. Reports and studies during on COVID-19 showed that both the very low and too high concentration of vitamins B and D, micronutrients and minerals make the human body vulnerable to chronic diseases or infections [ 35 , 36 , 37 , 38 ]. Indeed, we also found that the dietary intake of methyl-donors such as methionine, B6, B9 and the summative amounts of methyl-donor intakes (SUM MD) in terms of RDA levels significantly increased the overall survival of breast and colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Initial investigations were primarily focused on the molecular pathology of SARS-CoV-2 infection; however, later investigations demonstrated the involvement of nutritional deficiencies and neuropsychiatric illnesses in worsening the COVID-19 pathological manifestations. Moreover, the impact of social measures to prevent spread of SARS-CoV-2 infection drive the psychological derailment; and is also suggested to be considered for effective management of the COVID-19 pandemic (Girdhar et al, 2020;Soni et al, 2020b,d;Kumar and Nayar, 2021;Mehta et al, 2021;Nadalin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The investigators hypothesized a link between ingesting foods with high anti-ACE activity and having a low COVID-19 mortality rate (Nadalin et al, 2021). Few of the countries with low mortality rates such as Bulgaria, Greece, and Turkey record for consumption of fermented milk, which is known to be an organic ACE inhibitor.…”
Section: Role Of Altered Immune Responsementioning
confidence: 99%
“…Given that psychiatric conditions have been found to be risk factors for severe COVID-19 (19) and that severe COVID-19 is associated with higher rates of long COVID (3,9), it is possible that any increased risk of long COVID associated with preexisting psychiatric conditions is due to increased severity of infection. A secondary analysis was conducted to control for severity of infection by controlling for hospitalization acutely after COVID-19 infection to examine only mild COVID-19 cases (queries and analysis found in Supplementary Materials, http://links.lww.com/ PSYMED/A995).…”
Section: Methodsmentioning
confidence: 99%